Chromatin modifications of hTERT gene in hTERT-immortalized human mesenchymal stem cells upon exposure to radiation - ORUN, OYA; MEGA TİBER, PINAR (ELSEVIER SCIENCE BV, 2018)
Regulation of telomerase activity is thought to participate in the cellular response to ionizing radiation. Epigenetic mechanisms play a role in this regulation, as well as other mechanisms such as transcription, phosphorylation, etc. Here, we investigated chromatin modifications in telomerase promoter upon exposure to ionizing radiation in human mesenchymal stem cells (hMSC) and telomerase-immortalized hMSCs (hMSC-telo1) together with a hMSC-telo1 cell line in which TRF2 expression was partially repressed (siTRF2 hMSC-telo1). Histone methylations and acetylations were compared in all cell lines after exposure to various doses of ionizing radiation (0.1, 1, 2.5 and 15 Gy) using chromatin immunoprecipitation assay. hTERT gene was shown to be quickly regulated through H3, H4 acetylations, as well as with H3K4 and H3K9 methylations, following radiation exposure, although the kinetic of hMSC-telo1 cells were different, indicative of the higher radioresistivity of these cells. To the author's surprise, there was an upregulation of endogenous telomerase activity in the hMSC-telo1 cells, even though the cells had already expressed high levels of ectopic hTERT. Our results show that telomerase regulation is one of the primary actions in response to damage and epigenetic factors play a major role in this regulation. Our results also suggested that partial silencing of TRF2 enhances the radiosensitivity of these cells, and endogenous telomerase is upregulated upon radiation, even under ectopic expression of hTERT in these cells.
Keywords: Epigenetics; Chromatin modifications; hMSC; hTERT gene; Radiation; EPIGENETIC REGULATION; TRANSCRIPTION FACTORS; IONIZING-RADIATION; CATALYTIC SUBUNIT; TELOMERASE HTERT; HUMAN CANCER; IMMUNOPRECIPITATION; EXPRESSION